Team climate in primary health care: a systematic review of the literature - Vasconcelos, Jader (2024)
Introduction: Evaluating team climate is crucial in identifying challenges that health teams face when implementing interprofessional work processes. Objective: The aim of this study was to determine what the team climate in PHC is and whether there is an association between the team climate factor and the quality of care offered to the user. Methods: This study aimed to conduct a systematic literature review to define primary health care team climate and determine whether an association exists between team climate and healthcare quality. The protocol was registered under protocol number CRD 42019133389 with the International Prospective Register of Systematic Reviews (PROSPERO). A search for articles on team climate in primary health care was conducted using any version of the team climate inventory instrument in six databases. There were no restrictions on the publication date or language (Spanish, English, and Portuguese). Results: Of the 1,106 studies obtained after removing duplicates, 23 were selected for a full reading based on abstract evaluations. It was observed that teams with better work climates achieved better health care outcomes. However, due to methodological heterogeneity between studies, it was not possible to determine an average value for primary health care team climate as initially proposed. Conclusions: The study concluded that, although there are indications of a possible positive association between the team climate and the quality of health care in primary health care settings, there are still not enough studies to allow us to categorically state that this association exists.